Characterization of gut microbiota dysbiosis of diarrheic adult yaks through 16S rRNA gene sequences - Wu, Zhou-Lin; Wei, Ranlei; Tan, Xueqin; Yang, Danjiao; Liu, Dayu; Zhang, Jiamin; Wang, Wei (Frontiers in Veterinary Science, 2022)
Ruminant gut microbial community has a strong impact on host health and which can be altered during diarrhea disease. As an indigenous breed of Tibetan Plateau, domestic yak displays a high diarrhea rate, but little research has been done to characterize the bacterial microbial structure in diarrheic yaks. In the present study, a total of 30 adult yaks, assigned into Diarrhea (case, N=15) and Healthy (control, N=15), were subjected to gut microbiota profiling using V3-V4 region of 16S rRNA gene. The results showed that the gut microbiome of case group had a significant decrease in the alpha diversity. Additionally, differences in beta diversity were consistently observed for case and control group, indicating that the microbial community structure was changed due to the diarrhea. Bacterial taxonomic analysis indicated that the Bacteroidetes, Firmicutes, and Proteobacteria were the three most dominant phyla in both groups but different in relative abundance. Specially, the proportion of Proteobacteria in the case group was increased as compared with the control group, whereas Spirochaetota and Firmicutes were significantly decreased. At the genus level, the relative abundance of Escherichia-Shigella and Prevotellaceae_UCG-003 dramatically increased, whereas that of Treponema, p-2534-18B5_gut_group, and Prevotellaceae_UCG-001 observably decreased with the effect of diarrhea. Furthermore, based on our LEfSe results, Alistipes, Solibacillus, Bacteroides, Prevotellaceae_UCG_003, and Bacillus were significantly enriched in case group, while other five genera including Alloprevotella, RF39, Muribaculaceae, Treponema, and Enterococcus were the most preponderant in control group. In conclusion, alterations in gut microbiota community composition were associated with yak diarrhea, differentially represented bacterial species enriched in case animals providing a theoretical basis for establishing a prevention and treatment system for yak diarrhea.